Clinical efficacy of probiotics in improving intestinal mucosal permeability for functional dyspepsia patients with anxiety - Huang, Kang-ming; Qiu, Hua-bin; Liao, Dong-ping; Jiang, Ya-yue; Deng, Ying-Han; Chen, Hong-bin (Frontiers in Microbiology, 2025)
BackgroundThe aim of this study was to investigate whether probiotics are effective in improving symptoms of functional dyspepsia (FD) accompanied by anxiety.MethodsThere were 116 patients with FD accompanied by anxiety and 114 patients without anxiety. Each group was randomly divided into an intervention group and a control group. The intervention group received probiotics in addition to conventional acid suppression and gastric protection, as well as prokinetic treatments. The control group received conventional treatment plus a placebo.ResultsBefore treatment, significant differences were observed in IL-1, IL-6, TNF-α, LPS, Zonulin, DAO, and I-FABP between patients with FD accompanied by anxiety and those without anxiety (p < 0.05). Following the intervention with probiotics, the group with FD and anxiety experienced significant decreases in IL-1, IL-6, TNF-α, LPS, Zonulin, and DAO (p < 0.001), as well as significant reductions in the Patient Assessment of Gastrointestinal Disorders-Symptom Severity Index (PAGI-SYM) and the Hamilton Anxiety Scale (HAMA) scores (p < 0.001). In contrast, the intervention group with FD but without anxiety had significant reductions in IL-6 and TNF-α (p < 0.05), along with a significant decrease in the PAGI-SYM score (p < 0.001). Binary logistic regression analysis further revealed that lower I-FABP values (OR = 0.999, p = 0.036), lower LPS values (OR = 0.998, p = 0.013), and probiotic intervention (OR = 5.138, p = 0.000) were significantly associated with symptom relief.ConclusionThe intervention significantly improved the symptoms and anxiety scores of patients with FD and anxiety, and the changes in intestinal mucosal permeability indexes were closely related to symptom relief and anxiety improvement, Probiotic interventions may be an effective means of improving symptoms in patients with FD.Clinical trial registrationidentifier ChiCTR2300077847 https://www.chictr.org.cn/.